2001
DOI: 10.1901/jaba.2001.34-221
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and Distal Effects of Play on Child Compliance With a Brain‐injured Parent

Abstract: Individuals with brain injury may experience severe cognitive and other impairments. For brain-injured parents, such deficits may be associated with child behavior problems, including noncompliance. We assessed the effects of a play period conducted by a brain-injured father on the compliance of his son, who had become uncooperative with his father after the injury. The child consistently demonstrated improved compliance during proximal and distal compliance sessions that followed father-son play periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…For example, Mace, Mauro, Boyajian, and Eckert (1997) reported that for some participants using praise alone as a consequence for compliance with high-p instructions did not lead to increased compliance with low-p instructions, whereas praise combined with tangible reinforcers did. Moreover, although Mace et al (1988) reported that the antecedent delivery of response-independent stimuli (praise) did not increase compliance, others have reported findings to the contrary, further suggesting that contact with reinforcement prior to a low-p instruction might be an important variable (e.g., Bullock & Normand, 2006;Ducharme & Rushford, 2001;Kennedy, Itkonen, & Lindquist, 1995). Of the published research, only Bullock and Normand conducted a formal preference assessment to identify the consequences used for compliance with the high-and low-p instructions.…”
mentioning
confidence: 99%
“…For example, Mace, Mauro, Boyajian, and Eckert (1997) reported that for some participants using praise alone as a consequence for compliance with high-p instructions did not lead to increased compliance with low-p instructions, whereas praise combined with tangible reinforcers did. Moreover, although Mace et al (1988) reported that the antecedent delivery of response-independent stimuli (praise) did not increase compliance, others have reported findings to the contrary, further suggesting that contact with reinforcement prior to a low-p instruction might be an important variable (e.g., Bullock & Normand, 2006;Ducharme & Rushford, 2001;Kennedy, Itkonen, & Lindquist, 1995). Of the published research, only Bullock and Normand conducted a formal preference assessment to identify the consequences used for compliance with the high-and low-p instructions.…”
mentioning
confidence: 99%
“…Similar types of antecedent manipulations have been used with success to decrease challenging behavior of persons with DD (Ducharme and Rushford 2001), and there is some research to suggest that this might be a useful approach for addressing ISB in individuals with DD. For example, Cihak et al (2007) evaluated an antecedent manipulation in the form of an instructional revision to eliminate inappropriate selftouching in a 16-year-old female with a moderate intellectual disability.…”
Section: Instructional Revisionsmentioning
confidence: 99%
“…Any interventions for a TBI population should be flexible and pragmatic, adjusted to the cognitive and mental health issues of persons with TBI. And while not found in this population possible impulse control issues should be recognised, because they may present an increased risk for child abuse, and finally, the family should be involved, recognising the important role of family dynamics regarding the impact of TBI (Ducharme, 2003;Ducharme & Davidson, 2004;Ducharme & Rushford, 2001;Ducharme, Spencer, Davidson, & Rushford, 2002;Weatherhead & Newby, 2008).…”
Section: Implications and Conclusionmentioning
confidence: 99%